PENGARUH KUALITAS JASA DAN KEPUASAN NASABAH TERHADAP KEPERCAYAAN DAN LOYALITAS NASABAH KUR MIKRO BANK BRI KOTA DUMAI - Eko Saputra; Zulkarnain Zulkarnain; Samsir Samsir (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this study was to analyze the influence of Service Quality, and Satisfaction Against Trust and Customer Loyalty KUR Mikro Bank BRI Kota Dumai. As for the population in this study are all KUR Mikro Bank BRI Kota Dumai totaling 3310 people. Sampling using proportional random sampling method. The sample in this study amounted to 97 customers of KUR Mikro Bank BRI Kota Dumai using Slovin formula. Technique of collecting data using questioner which contains statements based on the variables studied. Data analysis technique used in this research is Structural Equation Modeling (SEM) based on variance-PLS. From the research results obtained conclusion as follows: 1) Quality Service Service has a positive and significant impact on Customer Trust. 2) Customer Satisfaction has a positive and significant impact on Customer Confidence. 3) Service Quality has a positive and significant impact on Customer Loyalty. 4) Customer Satisfaction has a positive and significant impact on Customer Loyalty. 5) Customer Confidence has a positive and significant impact on Customer Loyalty. 6) Service Quality has a positive and significant impact on Customer Loyalty through Customer Confidence. 7) Customer Satisfaction has a positive and significant impact on Customer Loyalty through Customer Trust.